PENGARUH VARIASI BENTUK BULBOUS BOW TERHADAP KOMPONEN HAMBATAN - Zaid Taqiya Robbani (2022)
As the development of shipbuilding technology began to show a better direction, ships as a means of sea transportation were the main choice of service users in transporting larger capacities. This study aims to analyze and compare the resistance of Roro ships on bulbous bows with the CFD method and variations already made with resistance influenced by the components of friction force, pressure, wave power, and liquid density. The model used is a Roro cargo vehicle which has been added a bulbous bow. Ship resistance analysis using the Computational Fluid Dynamics method with a speed variation of 13.5 knots ; 14.5 knots ; 15.5 knots; 16.5 knots; 17.5 knots, and high speed at fn 0.6 ; 0,8 ; and 1.0. This study obtained effectiveness in the bulbous bow variation model with a length of 2 meters which has a smaller resistance component value than the other 3 models. It is hoped that this research can be further developed and provide an understanding of ship resistance with bulbous bow variations.